No redshift evolution of non-repeating fast radio burst rates. Issue 3 (19th August 2020) - Hashimoto, Tetsuya; Goto, Tomotsugu; On, Alvina Y L; Lu, Ting-Yi; Santos, Daryl Joe D; Ho, Simon C-C; Kim, Seong Jin; Wang, Ting-Wen; Hsiao, Tiger Y-Y
ABSTRACT: Fast radio bursts (FRBs) are millisecond transients of unknown origin(s) occurring at cosmological distances. Here we, for the first time, show time-integrated-luminosity functions and volumetric occurrence rates of non-repeating and repeating FRBs against redshift. The time-integrated-luminosity functions of non-repeating FRBs do not show any significant redshift evolution. The volumetric occurrence rates are almost constant during the past ∼10 Gyr. The nearly-constant rate is consistent with a flat trend of cosmic stellar-mass density traced by old stellar populations. Our findings indicate that the occurrence rate of non-repeating FRBs follows the stellar-mass evolution of long-living objects with ∼Gyr time-scales, favouring e.g. white dwarfs, neutron stars, and black holes, as likely progenitors of non-repeating FRBs. In contrast, the occurrence rates of repeating FRBs may increase towards higher redshifts in a similar way to the cosmic star formation rate density or black hole accretion rate density if the slope of their luminosity function does not evolve with redshift. Short-living objects with ≲Myr time-scales associated with young stellar populations (or their remnants, e.g. supernova remnants, young pulsars, and magnetars) or active galactic nuclei might be favoured as progenitor candidates of repeating FRBs.